A note on improved differentiability for the Banach-space valued Finsler $γ $-Laplacian - Goering, Max; Koch, Lukas (Comptes Rendus. Mathématique)
We obtain improved fractional differentiability of solutions to the Banach-space valued Finsler $γ $-Laplacian defined on a $σ $-convex, $τ $-smooth Banach space. The operators we consider are non-linear and very degenerately elliptic. Our results are new already in the $\mathbb{R}$-valued setting.